A Facile Liquid‐Phase, Solvent‐Dependent Exfoliation of Large Scale MoS2 Nanosheets and Study of Their Photoconductive Behaviour for UV‐Photodetector Application. Issue 41 (2nd November 2021) - Sharma, Rohit; Kumar, Ashish; Kumari, Reena; Garg, Preeti; Umapathy, G.; Laisharm, Radhapiyari; Ojha, Sunil; Srivastava, Ritu; Sinha, Om Prakash
Abstract: Two‐dimensional MoS2 can be used for various electronic and optoelectronic applications due to its atomically thin structure and high surface area. Keeping such applications in mind, we report, the role of different solvent in the synthesis of 2D‐MoS2 nanosheets (NSs) via liquid‐phase exfoliation method, and these nanosheets are further studied for photodetector application. Bulk MoS2 powder has been exfoliated in various solvents like deionized water (DI), 1, 2‐dichlorobenzene (DCB), dimethylformamide (DMF), and N‐methyl‐pyrrolidone (NMP). The structural and optical properties of samples have been investigated. From the structural analysis, it has been found that MoS2 NSs have lateral dimensions in micron and are few nanometer thick. These NSs are single plane oriented with a 2H phase, which have semiconducting nature. The optical properties of MoS2 NSs have been studied by UV‐Visible absorption spectroscopy, and it is found that the optical band gap has been varied between 1.62 eV to 1.78 eV. The photoresponse of these synthesized NSs has been studied and found that NSs exfoliated in DMF and NMP show better photoresponse. Abstract : In this report, we have discussed the synthesis of 2D‐MoS2 via liquid‐phase exfoliation of the MoS2 powder using different solvents, i. e., deionized water (DI) 1, 2‐dichlorobenzene (DCB), Dimethylformamide (DMF) and N‐methyl‐pyrrolidone (NMP). The structural, optical and photo electrical properties of synthesized MoS2 nanosheets have been studied. we have found the negative photoconductivity (NPC) and self‐powered behavior in the MoS2 Nanosheets exfoliated in DI‐water, DCB, Dimethylformamide DMF except for MoS2 nanosheets exfoliated in NMP.